2019
DOI: 10.14202/vetworld.2019.1033-1038
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diversity of the invA gene obtained from human and egg samples

Abstract: Background and Aim: Salmonellosis is one of the most common foodborne bacterial diseases in the world. The great majority of Salmonella infections in humans are foodborne with Salmonella enterica and Salmonella Typhimurium accounting for a major part of the problem. The objective of this study was to investigate the presence of invA gene in strains of Salmonellae isolated from eggs and diarrheal swabs from human cases. In addition, the relationship between invA gene nucleotide sequences from different sources … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 23 publications
3
17
1
1
Order By: Relevance
“…The pathogenesis of Salmonella is due to a combination of chromosomal and plasmid-mediated factors. A number of genes such as invA , fimA , stn and spv account for salmonellosis, of which the chromosomally located invasion ( invA) gene codes for a protein in the inner membrane of the bacterium, which is necessary for invasion of the host epithelial cells [ 11 , 12 ]. In the present study, detection of the invA gene in 10 tested Salmonella isolates indicated their pathogenic nature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of Salmonella is due to a combination of chromosomal and plasmid-mediated factors. A number of genes such as invA , fimA , stn and spv account for salmonellosis, of which the chromosomally located invasion ( invA) gene codes for a protein in the inner membrane of the bacterium, which is necessary for invasion of the host epithelial cells [ 11 , 12 ]. In the present study, detection of the invA gene in 10 tested Salmonella isolates indicated their pathogenic nature.…”
Section: Discussionmentioning
confidence: 99%
“…However, the invasion gene invA , commonly involved in bacterial virulence, is also routinely used for the accurate detection of Salmonella spp. in clinical samples [ 11 ]. The nucleotide sequences of the invA gene are distinctive to the genus Salmonella , and the amplification of the invA gene by the polymerase chain reaction (PCR) is a suitable diagnostic method of detection of Salmonella due to its reliability, sensitivity, specificity and detection speed [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The invA gene is primarily targeted for the identification of Salmonella in food of animal origin, since it is present in pathogenic serovars and has been demonstrated to be a rapid and effective method for diagnosis of salmonellosis ( Karmi, 2013 ; Carraturo et al, 2016 ). However, there are few reports on the absence of invA gene in certain Salmonella strains, which indicate that they are not invasive or may have other invasive mechanisms ( Kaushik et al, 2014 ; Sharma and Das, 2016 ; Buehler et al, 2019 ; Kadry et al, 2019 ; Yanestria et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular methods were optimized for rapid identification of Salmonella isolates and its resistance genes in poultry using specific primers followed by nucleotide sequencing and phylogenetic analysis. The virulence of Salmonella is linked to a combination of various factors, for example, invA virulence gene in the inner membrane of bacteria that are necessary for invasion of epithelial cells (18, 19). In this study, detection of virulence invA gene (10 out of 10 isolates) in the isolated Salmonella indicates the pathogenic nature of these isolates.…”
Section: Discussionmentioning
confidence: 99%
“…However, the invA encoding invasion gene, commonly involved in bacterial virulence, is accountable and routinely used for the detection of Salmonella spp. (18). Moreover, the invA sequences are distinctive to the genus Salmonella and diagnosed by polymerase chain reaction (PCR) is a preferred diagnostic method due to its reliable sensitivity, specificity and detection speed (19, 20).…”
Section: Introductionmentioning
confidence: 99%